1984
DOI: 10.1111/j.1525-1470.1984.tb00446.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Plantar Warts in ChOdren with a Salicylic Acid‐Podophyllin‐Cantharidin Product

Abstract: One hundred and twenty-one children with plantar warts were treated with a topical preparation containing salicylic acid, 30%; podophyllin, 5%; and cantharidin, 1%. One hundred patients or their families were reached 6 months to 1 year later. This treatment was effective in 81 cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
1
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 7 publications
0
24
1
1
Order By: Relevance
“…33 Cellulitis developed in 4 patients whose plantar warts were initially treated with a mixture of 1% cantharidin, salicylic acid, and podophyllin that was left on for 24 hours, and then the warts were debrided with silver nitrate. 26 In a retrospective study of 300 children with molluscum contagiosum treated with cantharidin, 90% of the patients experienced resolution of symptoms and an additional 8% noted some improvement. 30 The authors used 52.5 mg of cantharidin crystals mixed in 7.5-mL flexible collodion.…”
Section: Dermatological Uses Of Cantharidinmentioning
confidence: 99%
See 2 more Smart Citations
“…33 Cellulitis developed in 4 patients whose plantar warts were initially treated with a mixture of 1% cantharidin, salicylic acid, and podophyllin that was left on for 24 hours, and then the warts were debrided with silver nitrate. 26 In a retrospective study of 300 children with molluscum contagiosum treated with cantharidin, 90% of the patients experienced resolution of symptoms and an additional 8% noted some improvement. 30 The authors used 52.5 mg of cantharidin crystals mixed in 7.5-mL flexible collodion.…”
Section: Dermatological Uses Of Cantharidinmentioning
confidence: 99%
“…Cantharidin should be applied only in the office by a physician 26 or under the direct supervision of a physician. Although 1 report advocates home use of cantharidin for warts, we believe that home use should be strictly avoided, 28 because severe blistering can result from improper use, 24 and because ingestion, especially by children, can be fatal.…”
Section: Dermatological Uses Of Cantharidinmentioning
confidence: 99%
See 1 more Smart Citation
“…A hyperkeratotic wart should first be pared with a #15 scalpel blade, then destroyed with high-concentration salicylic acid (17 % liquid or 40 % plaster), cryotherapy with liquid nitrogen, or electrodesiccation with curettage [82][83][84][85][86][87][88]. A 2011 metaanalysis of pooled randomized controlled trials suggested that salicylic acid should be used as the first-line agent, and a combination of salicylic acid with aggressive cryotherapy as second-line treatment [89].…”
Section: Warts (Verrucae)mentioning
confidence: 99%
“…Salicylic acid-podophyllin-cantharidin combinations can be helpful for treating warts in children (81% effectiveness in one study). 8 Duct tape may have a role in treating VV. A study noted that of 51 patients, 26 (51%) were treated with duct tape and 25 (49%) were treated with cryotherapy; 22 patients (85%) in the duct tape arm vs. 15 (60%) in the cryotherapy arm had complete resolution of their VV; however, this has not been the case for me.…”
mentioning
confidence: 99%